2012
DOI: 10.1100/2012/140564
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication as a Tool for Training Apprentice Welders: A Study about Risk Perception and Occupational Accidents

Abstract: The present study has aimed to identify the perceptions of apprentice welders about physical, chemical, biological, and physiological risk factors to which they are exposed; identify types of occupational accidents involving apprentice welders; and report the development of a socioenvironmental education intervention as a tool for risk communication for apprentice welders. A quantitative study was performed with 161 apprentice welders in Southern Brazil in 2011. Data collection was performed via structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The results obtained by the present study are parallel to those obtained by Cezar-Vaz et al who carried out a similar study among apprentice welders. Their results indicated that apprentice welders with an occupational accident record had higher risk perception than those without an occupational accident record [15]. In another study carried out by Cezar-Vaz et al, to identify risk perception and the types of occupational accidents among gas station workers, the perception of chemical risk was reported more among workers having records of chemical risk-related occupational accidents [16].…”
Section: Discussionmentioning
confidence: 94%
“…The results obtained by the present study are parallel to those obtained by Cezar-Vaz et al who carried out a similar study among apprentice welders. Their results indicated that apprentice welders with an occupational accident record had higher risk perception than those without an occupational accident record [15]. In another study carried out by Cezar-Vaz et al, to identify risk perception and the types of occupational accidents among gas station workers, the perception of chemical risk was reported more among workers having records of chemical risk-related occupational accidents [16].…”
Section: Discussionmentioning
confidence: 94%
“…This practice also included the Health Promotion in Different Work Environments Programme (HPDWEP) [ 37 , 38 ] of LAMSA, the School of Nursing, the Federal University of Rio Grande, RS, Brazil. The HPDWEP consists of a set of coordinated actions and continuous shaft in promoting social and environmental health in different work environments, the environments of which are included in the study group's academic LAMSA.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, risk communication, along with public participation and conflict resolution, encourages the modification of individual and collective behavior in the face of events that pose risks to health [ 2 ]. The use of risk communication as a primary prevention tool is found in different working environments, such as among farmers [ 11 ], chemical industries [ 12 ], and technological education schools [ 13 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…This study’s aim was to apply the communication of risks in welding apprenticeship programs. The Laboratory of Socio-Environmental Process Studies and Collective Health Promotion (LAMSA) research group has developed research in this context in the Socio-Environmental Laboratory of Occupational Health at the School of Nursing, Federal University of Rio Grande [ 13 , 14 ]. The perceptions of welding apprentices concerning welding fumes as associated with respiratory and cardiovascular disorders was used to classify events that pose risks to health and that can be communicated in the apprenticeship process.…”
Section: Introductionmentioning
confidence: 99%